Pathogenetic Treatment of Gastritis as a Basis for the Prevention of Gastric Cancer in the Countries of the Commonwealth of Independent States: Literature Review and the Resolution of a Scientific Symposium Held in Minsk, Republic of Belarus, January, 27, 2018 - V. T. Ivashkin; I. V. Maev; J. V. Gorgun; K. S. Kaliaskarova; M. M. Karimov; A. V. Kononov; T. L. Lapina; N. A. Markaryan; M. S. Moldobaeva; S. I. Pimanov; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The aim of this literature review is to generalize existing approaches to the pathogenetic treatment of gastritis as a basis for the prevention of gastric cancer, as well as to submit a resolution of a scientific symposium that brought together gastroenterologists from a number of CIS countries.Background.  H. pylori infection is widespread in CIS countries. The proportion of infected adults in the population ranges from 60 % to over 90 %. This causes a high incidence of chronic gastritis and other diseases associated with H. pylori. In 2012, gastric cancer was recognized as the 3rd leading malignant disease in the Kyrgyz Republic and the Republic of Uzbekistan, 5th — in Belarus and Kazakhstan, 6th — in Armenia and the Russian Federation. According to the standardized cancer mortality rate, gastric cancer takes the 1st place in Kyrgyzstan and Uzbekistan, 2nd — in Belarus, 3rd — in Kazakhstan, and 4th — in Armenia and Russia. In every case of H. pylori detection, it is important to make a decision about the expediency of eradication therapy. This is particularly significant, since H. pylori eradication has been recognized as an effective method of gastric cancer prevention. In addition, H. pylori eradication therapy in patients suffering from chronic gastritis with dyspepsia symptoms serves as the firstchoice therapy that allows patients with dyspepsia resulting from H. pylori infection to be excluded. The choice of the H. pylori eradication therapy scheme is determined by the protocols (standards) of patient management accepted in the respective CIS country. A high efficacy of H. pylori infection eradication is shown to be provided by bismuthcontaining schemes.Conclusion.  Opportunistic screening of H. pylori is carried out by general practitioners, district physicians, gastroenterologists and other specialists. The most effective method of gastric cancer prevention is the eradication therapy of H. pylori infection in chronic gastritis. The maximal positive potential of such a therapy is realized when it is performed before the atrophic changes of the gastric mucosa have appeared.